Recent Investigations on the Pharmacology, Phytochemistry, and Traditional use of the Solanum Nigrum Linn - Shukla, Rahul (B R Nahata Smriti Sansthan International Journal of Phramaceutical Sciences & Clinical Research, 2024)
The Solanum nigrum Linnaeus plant was first cultivated in Southeast Asia, but it is now grown all over the world and is now widespread across the continents of Europe, Asia, as well as North and South America, and it thrives in climates ranging from temperate to tropical. One hundred and eighty-eight different chemical components of S have been recognized up until this point nigrum. Investigations into the physiological and psychoactive effects of S. Studies conducted in vitro and in vivo on the medicinal herb nigrum have revealed that it possesses a variety of beneficial qualities, including those that are neuroprotective, antibacterial, anti-inflammatory, and anticancer. This article takes a detailed and methodical approach to discuss the traditional and botanical applications of S, as well as its phytochemical components, pharmacological properties, clinical trial results, and adverse effects. Nigrum to provide the most recent facts possible regarding the application and utilization of S. nigrum as an ingredient in therapeutic meals and drugs.